2013
DOI: 10.1016/j.eurpsy.2012.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Looking at my body. Similarities and differences between anorexia nervosa patients and controls in body image visual processing

Abstract: Our findings suggest the existence of a continuum from normalcy to pathology in neural response to body image, and confirm the clinical relevance of body image distortion in AN, reinforcing the key role of attentive, executive and self-evaluation networks in AN visual processing of own distorted body image.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 51 publications
(88 reference statements)
5
60
0
1
Order By: Relevance
“…3B), and increased RD in bilateral IFO (Fig. 3D) are consistent with abnormal body perceptions and frontooccipito-parietal functionality in anorexia nervosa [42,43]. Similar to others [44], our findings appear largely left-lateralized although increased right IFO RD also supports right parietal involvement [43,45].…”
Section: Scc Connectivity Is Different Between Anorexia Nervosa and Csupporting
confidence: 92%
“…3B), and increased RD in bilateral IFO (Fig. 3D) are consistent with abnormal body perceptions and frontooccipito-parietal functionality in anorexia nervosa [42,43]. Similar to others [44], our findings appear largely left-lateralized although increased right IFO RD also supports right parietal involvement [43,45].…”
Section: Scc Connectivity Is Different Between Anorexia Nervosa and Csupporting
confidence: 92%
“…thinness), the higher activations presented by the amygdala and PFC to overweight body images may occur due to 'top-down' cognitive mechanisms to help reducing the effects of stimuli considered to be threatening by these patients. This is consistent with previous studies reporting prefrontal activity in response to oversized body images [18].…”
Section: Neurocircuitry Of Reward and Inhibitionsupporting
confidence: 83%
“…Vocks and colleagues have also found that AN patients revealed enhanced limbic activity (amygdala) when looking to other women's body, which may be related to stronger emotional affective reactions, probably due to unfavourable social comparison processes [17]. One study using participants' distorted body images as stimuli have shown that when AN patients see themselves as oversized, there is a higher activation in regions such as the extrastriate body area, superior and inferior parietal lobule and prefrontal areas, which may be the result of higher affective value given to oversized body image [18].…”
Section: Neurocircuitry Of Cognitive and Emotional Processing Of Visumentioning
confidence: 99%
“…In contrast, several studies in the field of eating disorders found differences regarding the exploration pattern of body stimuli in anorexia nervosa (e.g. [30,31,32,33,34]) and bulimia nervosa (e.g. [34,35,36,37]) compared to healthy controls.…”
Section: Discussionmentioning
confidence: 94%